2018
DOI: 10.31557/apjcp.2018.19.12.3451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphism and Expression Profile of ASIC1 and IL-6 Genes in Patients with Gastric Cancer

Abstract: : Gastric cancer is one of the most common upper gastrointestinal malignancies. Some Iranian provinces, such as in the northern and northwestern areas, are at a high risk, whereas the central and western provinces are at a medium and the southern regions at low risk. This study was carried out to estimate the impact of the expression patterns of ASIC1 and IL-6 genes and the IL-6rs-174 and ASIC1rs 7562468… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…IL-6 gene has been extensively studied in the development of GC, because inflammation and cancer are directly connected ( 13 , 23 ). Inflammatory processes, such as that caused by H. pylori infection, increase the synthesis of IL-6, activating the immune response and signaling pathways, which may contribute to the development of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 gene has been extensively studied in the development of GC, because inflammation and cancer are directly connected ( 13 , 23 ). Inflammatory processes, such as that caused by H. pylori infection, increase the synthesis of IL-6, activating the immune response and signaling pathways, which may contribute to the development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In results that were consistent with ours, the expression of IL-6 was related to the promotion of human GC invasion and migration of AGS cells. Immunohistochemistry and in-situ hybridization have shown that IL-6 is highly expressed and is secreted from both gastric epithelial cells and inflammatory cells infiltrating the gastric mucosa in H. pylori infection ( 23 ). Zuo et al ( 27 ) obtained similar results, with greater expression in the cancer group than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was concluded that downregulation of ASIC1 inhibits the growth of GC by reducing autophagy [112]. Subsequent studies have shown that the expression of ASIC1 exhibits a significant correlation with an increased risk of GC as well as with GC cell migration and invasion [113,114]. Thus, hypoxia causes acidification of the extracellular environment, which in turn promotes the opening of the ASIC1 channel and ultimately regulates GC through autophagy.…”
Section: Hypoxia Promotes the Opening Of Asic1 Channels Which Regulate Gc Through Autophagymentioning
confidence: 99%